1993
DOI: 10.1007/bf01517045
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumour growth in the rat liver after selective elimination of Kupffer cells

Abstract: The evidence that Kupffer cells are capable of controlling metastatic growth in the liver in vivo is largely circumstantial. The best approach when studying natural cytotoxicity activities of Kupffer cells is to investigate the effect of Kupffer cell elimination on tumour growth. Until now it has not been possible to eliminate Kupffer cells without affecting other cell populations. We have recently developed a new method to eliminate Kupffer cells selectively: intravenous injection of liposome-encapsulated (di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 29 publications
3
62
0
2
Order By: Relevance
“…Moreover, the addition of Cl 2 MDP-L had no effect on the viability of hepatocytes in vitro (assessed in terms of aspartate aminotransferase activity released into the culture medium over a 48-h incubation period) or the capacity of cultured hepatocytes to support the intracellular growth of Listeria (21 ; flow cytometric analysis, control listed first). These data are consistent with the results of numerous other studies that failed to show a significant effect of Cl 2 MDP-L on hepatocytes or circulating white blood cells, i.e., lymphocytes, granulocytes (including neutrophils), or mononuclear phagocytes (9,(22)(23)(24)(25) (26 -31). Conjugated mAbs used in flow cytometric analyses to characterize the NPC populations derived from control and Cl 2 MDP-L-treated mice were purchased from PharMingen (San Diego, CA).…”
Section: Kupffer Cell Depletionsupporting
confidence: 92%
“…Moreover, the addition of Cl 2 MDP-L had no effect on the viability of hepatocytes in vitro (assessed in terms of aspartate aminotransferase activity released into the culture medium over a 48-h incubation period) or the capacity of cultured hepatocytes to support the intracellular growth of Listeria (21 ; flow cytometric analysis, control listed first). These data are consistent with the results of numerous other studies that failed to show a significant effect of Cl 2 MDP-L on hepatocytes or circulating white blood cells, i.e., lymphocytes, granulocytes (including neutrophils), or mononuclear phagocytes (9,(22)(23)(24)(25) (26 -31). Conjugated mAbs used in flow cytometric analyses to characterize the NPC populations derived from control and Cl 2 MDP-L-treated mice were purchased from PharMingen (San Diego, CA).…”
Section: Kupffer Cell Depletionsupporting
confidence: 92%
“…Although myeloid cells have been implicated as having a role in surveillance and prevention of hepatic metastases, [1][2][3][4] it is unclear what role, if any, they play in the rejection of established tumors. Using flow cytometry, we found that a significantly higher proportion of cells of hematopoietic origin (CD45 ϩ ) isolated from tumor-bearing liver had a mature granular phenotype (high FSC:SSC, CD34 Ϫ ).…”
Section: Discussionmentioning
confidence: 99%
“…Mature cells of the hematopoietic system of both myeloid (monocytes and neutrophils) and lymphoid (T cells, natural killer [NK], and murine NK1.1 cells) lineages are thought to play a role in the host response to tumor challenge. [1][2][3][4][5][6][7][8][9][10] Hepatic hematopoiesis, in adult mice, has been shown to be important in the generation of antitumor effector cells. 6,7,11,12 While the hematopoietic function of the liver in the human fetus is well documented, 13 the role of the adult human liver (AHL) in hematopoiesis is thought to be relatively minor.…”
mentioning
confidence: 99%
“…28 Briefly, a small median laparotomy is performed while the animal is under general anaesthesia (intramuscular injection of 0.8 mL ketamine 10% plus 0.2 mL mL medium was injected in a mesenteric vein. (2) a control thiazine) and a loop of small bowel is exposed.…”
Section: Experimental Designmentioning
confidence: 99%